Effects of atmosphere and blending ratios on emission characteristics of pollutants from co‐combustion of municipal solid waste and aged refuse. Issue 2 (14th February 2022) - Li, Debo; Feng, Yongxin; Chen, Zhihao; Chen, Zhaoli; He, Hanyan; Zhang, Yaqi; Du, Binyun; Yu, Zhaosheng
Abstract: The emission of pollutants caused by incineration has imposed a severe burden on the atmospheric environment. In this study, the thermogravimetric thermal analyzer (TGA) was used to study the characteristic behavior of co‐combustion of municipal solid waste (MSW) and aged refuse (AR). And combined with Fourier transform infrared measurement, the emissions of several typical gaseous pollutants (NO, CO x, CH4, HCl, HCN, SO2 ) have been investigated. Also, the release characteristics of heavy metals (As, Cd, Co, Cr, Cu, Ni, Pb, Zn, Ti) during the co‐combustion process were explored using inductively coupled plasma–optical emission spectrometry (ICP‐OES). This research found that both the combustion atmosphere and the mixing ratios impacted the experimental results. As the proportion of AR in the blends increased, the ignition index decreased, the burnout temperature rose, but the burnout efficiency increased. The addition of AR inhibited the generation of CO2, CH4, and HCl and promoted the production of NO and CO. Aerobic environment mainly inhibited the release of Cr and Mn. The research results provided important information for the study of pollutant emission characteristics during the co‐combustion of MSW with AR.